Plantar Support Adaptations in Healthy Subjects After Eight Weeks of Barefoot Running Training - Sanchez-Ramirez, C (PeerJ Inc., 2020)
Background: Although the studies of barefoot running have intensified, it is still missing longitudinal work analyzing the effects of barefoot running on the phases of plantar support. The objective of this research was to analyze the modifications undergone by the Total Foot Contact (TFC) phase and its Flat Foot Phase (FFP) in subjects beginning the practice of barefoot running, in its acute and chronic effects. Methods: A total of 28 subjects were divided into the Barefoot Group (BFGr) (n = 16) and the Shod Group (SHGr) (n = 12), evaluated before (Baseline) and after running for 20 min at 3.05 ms-1 (Post 20 min Running), and at the end of a running training protocol with an 8-week long progressive volume (Post-8-week Training). The dynamic plantar support was measured with a baropodoscope. The duration of TFC (ms), the moment at which the FFP occurred, the maximum surface of TFC (MSTFC) (cm2), the FFP surface (SFFP) (cm2), the peak pressure of TFC (PP-TFC) (kgcm-2), and the peak pressure of FFP (PP-FFP) (kgcm-2) were recorded. The 3 × 2 ANOVA analysis was made to determine the effects and interactions that the condition produced (Shod/Barefoot), and the time factor (Baseline/Post 20 min Running/Post-8-week Training). Results: The condition factor caused more significant effects than the time factor in all the variables. Duration of TFC in BFGr showed significant differences between the Baseline and Post-8-week Training (p = 0.000) and between Post-20-min Running and Post-8-week Training (p = 0.000), with an increasing trend. In the moment at which the FFP occurred a significant increase (p = 0.029) increase was found in Post-20 min Running (48.5%) compared to the Baseline (42.9%). In MSTFC, BFGr showed in Post-8-week Training values significantly higher than the Baseline (p = 0.000) and than Post-20-min Running (p = 0.000). SHGr presented a significant difference between the Baseline and Post-8-week Training (p = 0.040). SFFP in BFGr modified its values with an increasing trend (p = 0.000). PP-TFC in BFGr showed a significant decrease (p = 0.003) in Post-8-week Training (1.9 kgcm-2) compared to the Baseline (2.4 kgcm-2). In PP-FFP significant decreases were recorded in BFGr and between Post-8-week Training and Baseline (p = 0.000), and Post-8-week Training and Post 20 min Running (p = 0.035). Conclusions: The adaptation took place after the 8-week training. The adaptations to running barefoot were characterized by causing an increase of the foot s plantar support in TFC and in FFP, as well as a decrease of the plantar pressure peak in both phases. Also, there is an increased duration of the TFC and FFP, which may be related to an acquired strategy to attenuate the impacts of the ground s reaction forces. © 2020 Sánchez-Ramírez and Alegre.